DISSOLUTION BEHAVIOR, STABILITY AND ANTI-INFLAMMATORY ACTIVITY OF KETOPROFEN COATED TRIPOLYPHOSPHATE MODIFIED CHITOSAN NANOPARTICLE - Jaya Hardi; Purwantiningsih Sugita; Laksmi Ambarsari (Universitas Gadjah Mada, 2013)
Ketoprofen coated tripolyphosphate modified chitosan nanoparticle was resulted from ionic gelation process by ultrasonication, centrifugation, and spray dry methods. Particle was analyzed by particle Size Analyzer. Dissolution and stability of them have conducted by Row Hansen methods at 37±0.5 °C and 150 rpm and using climatic chamber at 40±2 °C and relative humidity 75±5% for 3 months, respectively. Anti-inflammatory activities have conducted by Plate Reader methods. The result showed that B formulae have particles diameter of 563.1±157.5 nm and entrapment efficiency of 89.663%, respectively. Dissolution behavior showed that ketoprofen restrained released within acid medium and maximum released within base medium of 11.35-15.87% and 45.73-99.25%, respectively. Kinetically, dissolution of ketoprofen within intestinal and gastric pH condition was Korsmeyers-Peppas kinetic models. While, stability behavior showed that B formula has ketoprofen percentage left in nanocapsule after 3 months greater than 90% with water content and shelf life of 19.68%, and 14.19 week, respectively, and degradation kinetic model followed Avrami-Eroveef equation. Anti-inflammation test showed that B formula had the COX-2 inhibitory activity of 90.86% is higher than free ketoprofen.